Memahami Kearifan Lokal Masyarakat Minahasa, sebagai Upaya Membangun Harmonisasi Kehidupan Sosial Masyarakat - Umaternate, Abdul Rasyid; Fathimah, Siti; Hasrin, Awaluddin; Sidik, Sangputri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to identify the local wisdom of the Minahasa community. Local wisdom is an important part and has been rooted in society. This study uses a qualitative approach with data collection methods by observation and in-depth interviews. The results of the study show that there is local wisdom of the Minahasa community of Maesa-esa'an, Mangenang-puddle, Masawang-sawangan, Matombo- Kuncian, Malinga-lingaan, Mapalus, and Maleo-leosa. This local wisdom still exists in the Minahasa community. However, only parents understand, so efforts are needed to maintain this local wisdom